Ethics and newborn - Oliveros Donohue, Miguel (2015)
It has prompted major changes in neonatology. Advances in the field of medicine and technology allow the survival of infants who some years ago was impossible concebir1,4. These advances, however, have also brought discussions in the areas of morality, ethics and leyes1,8. The major conflicts have occurred with infants born with major birth defects, those born with low weight and extreme suffering severe perinatal asphyxia.